PENGARUH STRUKTUR MODAL TERHADAP NILAI PERUSAHAAN PADA PERUSAHAAN TEKSTIL DAN GARMEN - Khoirunnisa, Fairuz; Purnamasari, Imas; Tanuatmodjo, Heraeni (Business Education Program of Universitas Pendidikan Indonesia, 2018)
Purpose - The purpose of this research are to descript of capital structure and firm value, and to analyze the impact of capital structure to firm value at textile and garment companies for the period 2011-2015.Design / methodology / approach - Method in this research used descriptive and verification methods. Data that used are secondary data from fact book years 2011-2015 with analysis technique using simple linear regression. Sampling in this research use purposive sampling.Findings - The result showed that the capital structure has a positive effect to firm value.Originality -The difference of this research with previous research is on research object, population and research sample, research period, measuring instrument and research result.